Publiczna i pozarządowa pomoc społeczna w Rzeszowie - Wielgos-Struck, Renata; Bozacka, Małgorzata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
This article presents social service work and NGOs which operate in Rzeszow. It also focused on showing Municipal Social Welfare Center from perspective of its aims, organizational structure and staff. In addition to that, there is a characteristic of this social welfare center as well as its innovative approach to issues in the field of social work. The whole article is summarised by detailed descriptions of NGOs which operate in the social service shelters in Rzeszow. This non-governmental organizations are very important partners for public social welfare, because they can both solve social problems of town citizens.
Keywords: public social service; social welfare center in Rzeszow; non-governmental organizations (NGOs)